CREATIVE SELF EFFICACY DALAM MENYELESAIKAN MASALAH MATEMATIKA - Ayati, Julia Putri Riska; Afifah, Dian Septi Nur; Setiani, Rahyu (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
The success of students in solving math problems is supported by students' positive attitudes towards learning in the classroom such as interest, curiosity, and self-efficacy. Self efficacy greatly affects students' persistence in solving problems, based on this condition, students tend to be less confident in their own abilities, therefore researchers are interested in digging deeper into students' ability to solve mathematical problems. This article aims to describe creative self efficacy in solving problems based on polya stages. This study uses descriptive research with a qualitative approach. The research subjects were 2 students in grade VII A SMPN 2 Kalidawir who had the highest scores. The selection of research subjects is based on the results of the creative self efficacy questionnaire. Data collection techniques with questionnaires, test questions and interviews. Data analysis techniques with data reduction, data presentation and conclusion drawn. To test the validity of the data using triangulation methods and sources. The test results are analyzed with polya steps and indicators. The results showed that creative self efficacy in solving S-1 math problems met the polya stage of planning solutions, solving problems, and re-examination. Meanwhile, S-2 fulfills the polya stages of understanding the problem, planning the solution, solving the problem and re-examining. Furthermore, it is recommended to further examine creative self efficacy in solving mathematical problems with different theories, methods and materials. For teachers, it can be used as a reference to train students in solving mathematical problems.